A Study of Current Status of Drinking Water in Pokhara Metropolitan City of Nepal - Prasad, Ishwar; Adhikari, Rajendra P. (Journal of Engineering Technology and Planning, 2019)
Management of drinking water has been a global issue and has emerged as big challenge in cities especially for developing countries. Nepal is one of the least developed countries and all cities of the country is facing this challenge along with its capital city Kathmandu. Nepal has started implementing federal system with creation of seven provinces and 753 local governments. This study analyzes the current status of demand and supply of drinking water in Pokhara Metropolitan City, the second largest city of Nepal in terms of population and largest city in terms of area and forecasts the demand and supply of drinking water in the year 2021 and 2031in the city. Relevant formula has been used to forecast the demand and supply and published data were used for discussion and analysis. This study will help the concerned authority in forming its water related policy and will be beneficial for other growing cities as reference. This study revealed that water demand will reach 65 ml/d in 2021 and 108 ml/d in 2031. So, in the existing condition, the gap between demand and supply will continue in future also.